Emotion management in organizations: the transformation of unreachable feelings to modifiable communication in organizations - Tamara Freis (Frontiers in Education)
A fundamental challenge confronting modern organizations is to rationalize the affectivity of their members. In contrast to the 19th century, when communication in private settings was largely devoid of emotional content, the current era is characterized by a notable shift toward the incorporation of emotional elements in public discourse. This transformation is unfolding against the background of the ongoing evolution of modern organizations, with the processes of digitization and structural-automation contributing to this shift. The renewed emphasis on emotional semantics is facilitated by these developments—made possible by the fact that they facilitate the experience of the potential future obsolescence of humans as a source of crises. The concept of emotional semantics is currently being discussed in economic discourse, political debate, and in the context of management and leadership. Modern organizations mandate that their members manage their emotions through an organizational culture that fosters reflective communication through empathy. However, an understanding of this process can only be achieved through an examination of historical evidence. The article posits that organizations serve as pivotal actors in the domain of emotion management. Situated at the nexus of historical educational considerations, this perspective offers a nuanced interpretation of the historical evolution of organizational control ambitions. These ambitions have been catalyzed by contemporary trends, such as digitization and the integration of artificial intelligence and have undergone a progressive transformation over time. By sensitizing to the interplay of personal-psychic, institutional and organizational orders, the conceptual instruments for describing a history of emotions become more nuanced. This is demonstrated in the article through the analysis of specific organizational forms, which exemplify a parallel evolution within modern organizational society. Perspectives and discourses in organizational research provide novel approaches to the history of education by considering the organized nature of emotional phenomena. In this regard, the objective of the article is to provide impetus for the field of emotion-sensitive organization and management research which addresses questions pertaining to the transformation of organizations and their historical lines of continuity.